Preparation method of multifunctional phase change energy storage composite membrane with thermal management performance
Through microencapsulation of phase change materials and combining MXene nanosheets and chitosan technology, the problems of phase change material leakage and low thermal management efficiency were solved, and a phase change energy storage composite film with excellent thermal management performance was prepared, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411778586.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
Existing phase change materials are prone to leakage problems during solid-liquid transformation, which limits their further promotion in practical applications, especially to achieve effective thermal management of human body temperature under cold external temperature and low sunlight conditions.
Through micro-encapsulation technology, phase change material is encapsulated using inorganic silicone shells, combined with MXene nanosheets and chitosan, and a multifunctional phase change energy storage composite membrane with thermal management performance is prepared by physical blending and vacuum suction filtration.
It realizes effective leakage prevention of phase change materials, improves the mechanical properties and thermal management capabilities of the composite membrane, has appropriate phase change temperature, excellent phase change enthalpy and good thermal stability, and is suitable for warm-keeping materials and human photothermal treatment.
Smart Images

Figure CN119591913A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wearable energy storage materials, and in particular to a method for preparing a multifunctional phase-change energy storage composite film with thermal management performance. Background Art
[0002] The growing demand for energy has prompted people to seek renewable energy and new energy storage strategies. The combination of solar energy and phase change materials (PCMs) is a promising and efficient energy storage technology. PCMs, as latent heat storage materials, can store a large amount of heat during the phase change process. In recent years, organic solid-liquid phase change materials have become a hot topic in the field of phase change energy storage due to their advantages such as low supercooling and high enthalpy change value. However, due to the easy leakage problem during the solid-liquid transition process, its further promotion in practical applications is limited. Microencapsulation technology can not only prevent the leakage of organic phase change materials, but also the prepared organic phase change material microcapsules can be combined with fibers, coatings, plastics, adhesives and other substrates as a functional material to prepare composite materials that can be widely used in energy-saving buildings, smart fabrics, solar thermal collection, human medical care and other fields. Although microencapsulated phase change materials can achieve the role of temperature regulation, the thermal management driving method is relatively simple. It is a huge challenge to achieve effective thermal management of human body temperature under cold external temperatures and low sunlight. Therefore, combining photothermal materials with phase change materials to develop and prepare wearable products suitable for human thermal management functions has become the focus of current research. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present invention provides a multifunctional phase change energy storage composite film with thermal management performance and a preparation method thereof. The prepared phase change composite film can be applied to thermal insulation materials and human photothermal therapy, and has a suitable phase change temperature, excellent phase change enthalpy and good thermal stability.
[0004] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a multifunctional energy storage phase change composite film with thermal management performance, comprising the following steps:
[0005] S1. Preparation of phase change microcapsules
[0006] Phase change material, hexadecyltrimethylammonium bromide and formamide are mixed in a three-necked flask and heated and stirred in a water bath. Then, tetraethoxysilane is added to the mixture and continued to heat and stir. Subsequently, hydrochloric acid aqueous solution is dripped into the flask, stirred vigorously and aged. Finally, the synthesized product is filtered, washed and dried to obtain a phase change microcapsule product SiO2-MEPCM with excellent thermal storage performance.
[0007] S2. Preparation of Monolayer MXene
[0008] Ti3C2T was prepared by mixed acid etching x , pour the etchant and deionized water into a polytetrafluoroethylene liner for heating and stirring in a water bath, then add Ti3AlC2 in small amounts and multiple times, collect the solution and centrifuge until the pH of the solution is neutral, then add LiCl to the above solution and stir, collect the solution and centrifuge it several times, and the result is a single-layer MXene two-dimensional nanosheet;
[0009] S3. Preparation of composite membrane
[0010] The single-layer MXene two-dimensional nanosheet solution and the chitosan solution were mixed and stirred, and then the phase change microcapsule product was added and ultrasonicated to obtain a uniform mixture. Finally, vacuum filtration was performed to obtain a phase change energy storage composite film that can be used in thermal insulation materials and human photothermal therapy and has a suitable phase change temperature, excellent heat storage capacity and good thermal stability.
[0011] Preferably, in step S1, the phase change material is any one of hexadecane, octadecane and eicosane, the ratio of the phase change material to tetraethoxysilane is 1:1, the concentration of the added hydrochloric acid aqueous solution is 0.8 M, and the water bath temperature is 50-60°C.
[0012] Preferably, in the step S2, the etchant used is a mixed solution of fluoride and hydrochloric acid, wherein the fluoride is any one of sodium fluoride and lithium fluoride, the concentration of the hydrochloric acid is 9 mol / L to 12 mol / L, and the water bath heating temperature is 40 to 50°C.
[0013] Preferably, the single-layer MXene two-dimensional nanosheet is a two-dimensional regular sheet structure, and the thickness of the single-layer MXene two-dimensional nanosheet is 1.5 to 30 nm and the diameter is 2 to 10 μm; the surface of the phase change microcapsule product is smooth and the diameter is 2.5 to 3.5 μm.
[0014] The present invention provides a multifunctional phase-change energy storage composite film with thermal management performance and a preparation method thereof. It has the following beneficial effects:
[0015] 1. The present invention adopts a micro-encapsulation method to use an inorganic silicon shell to encapsulate the phase change material, which effectively prevents leakage of the phase change material. In addition, the encapsulation technology can also provide a larger heat transfer surface area, thereby improving the efficiency and effectiveness of the phase change material.
[0016] 2. The present invention effectively improves the mechanical properties of the composite film by combining MXene nanosheets with chitosan. Chitosan is a representative of natural positively charged polyelectrolytes. MXene nanosheets will combine with chitosan molecular chains through electrostatic interactions, thereby improving the mechanical properties of the composite material.
[0017] 3. The present invention adopts the method of physical blending and vacuum filtration to prepare the composite membrane, which is simple to operate, short in cycle and low in cost.
[0018] 4. The phase change composite film prepared by the present invention can be applied to thermal insulation materials and human photothermal therapy, and has a suitable phase change temperature, excellent phase change enthalpy and good thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 X-ray diffraction spectra of the single-layer MXene two-dimensional nanosheet, phase change microcapsule, chitosan, and composite film of the present invention;
[0020] Figure 2 SEM images of the single-layer MXene two-dimensional nanosheet film, the single-layer MXene two-dimensional nanosheet / chitosan film, and the composite film of the present invention, wherein a is a single-layer MXene two-dimensional nanosheet film, b is a single-layer MXene two-dimensional nanosheet / chitosan film, and c is a composite film;
[0021] Figure 3 is a DSC curve diagram of eicosane, phase change microcapsules and composite membranes of the present invention;
[0022] Figure 4 is a thermogravimetric graph of the composite film of the present invention;
[0023] Figure 5 It is a simulated thermal management curve diagram of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Embodiment 1:
[0026] The present invention provides a method for preparing a multifunctional energy storage phase change composite film with thermal management performance, comprising the following steps:
[0027] S1. Preparation of phase change microcapsules
[0028] 5g of phase change material, 0.8g of hexadecyltrimethylammonium bromide as a cationic surfactant and 60mL of formamide as a dispersion medium were mixed in a three-necked flask at 50°C and heated in a water bath for 4 hours. Then, 5g of tetraethoxysilane was added to the mixture as a silicon source, and then stirred continuously for 5h. Subsequently, 60mL of hydrochloric acid aqueous solution was dripped into the flask, stirred vigorously for 4 hours, and then aged at 50°C for 24 hours. Finally, the synthesized product was filtered, washed with deionized water and alcohol, and then dried at 35°C for 24 hours to obtain the phase change microcapsule product SiO2-MEPCM.
[0029] S2. Preparation of Monolayer MXene
[0030] Ti3C2T was prepared by mixed acid etching x , pour the etchant and deionized water into the polytetrafluoroethylene liner and heat and stir in a water bath for 30 minutes, then add 1g Ti3AlC2 in small amounts several times, stir for 24 hours, collect the solution and centrifuge until the pH of the solution is neutral, then add 2g LiCl to the above solution and stir for 24 hours in a water bath at 40°C. Collect the solution and centrifuge it several times to obtain a single-layer MXene two-dimensional nanosheet.
[0031] S3. Preparation of composite membrane
[0032] 25.7 ml of 0.7 mg / mL single-layer MXene two-dimensional nanosheet solution was mixed with 1.8 g of chitosan solution and stirred for 1 h, and then the phase change microcapsule product was added and ultrasonicated to obtain a uniform mixture. Finally, the composite membrane was obtained by vacuum filtration.
[0033] In step S1, the phase change material is any one of hexadecane, octadecane, and eicosane, the ratio of the phase change material to tetraethoxysilane is 1:1, and the concentration of the added hydrochloric acid aqueous solution is 0.8M.
[0034] In step S2, the etchant is a mixed solution of fluoride and hydrochloric acid, wherein the fluoride is any one of sodium fluoride and lithium fluoride, the mass ratio of fluoride to MAX phase material is 2:1, and the concentration of hydrochloric acid is 9 mol / L.
[0035] In this embodiment, scanning electron microscopy was used to compare and observe the morphology and microstructure of MXene two-dimensional nanosheets, MXene two-dimensional nanosheets / chitosan, and MXene two-dimensional nanosheets / chitosan / phase change microcapsule materials, and the crystal structures of MXene two-dimensional nanosheets, chitosan, phase change microcapsules, and composite films were discussed using XRD patterns. The heat storage capacity and thermal stability of the materials were explored by DSC and thermogravimetric tests, and the thermal management capacity of the materials was explored by simulated thermal management tests, and the test results were analyzed in conjunction with the accompanying drawings, as follows:
[0036] Figure 1 The X-ray diffraction spectra of the single-layer MXene two-dimensional nanosheet, phase change microcapsule, chitosan, and composite film of the present invention are, from bottom to top, single-layer MXene two-dimensional nanosheet (MXene), chitosan (CS), phase change microcapsule (PCC), and composite film (MCP); from Figure 1 It can be seen that the strong diffraction peak of chitosan is consistent with the XRD pattern reported in previous literature. The phase change microcapsules showed characteristic diffraction peaks at 19.4°, 23.3° and 24.8°, indicating good crystallization performance. In addition, the diffraction peaks of phase change microcapsules and single-layer MXene two-dimensional nanosheets were found in the XRD pattern of the composite film, and the position of the diffraction peaks did not move significantly, indicating that the phase change microcapsules and single-layer MXene two-dimensional nanosheets can still remain in the crystalline state in the composite film, which meets the characteristics of composite materials.
[0037] Figure 2 The SEM images of the single-layer MXene two-dimensional nanosheet film, the single-layer MXene two-dimensional nanosheet / chitosan film, and the composite film of the present invention are shown in Figure 1, wherein a is the SEM image of the single-layer MXene two-dimensional nanosheet film, b is the SEM image of the single-layer MXene two-dimensional nanosheet + chitosan film, and c is the SEM image of the composite film (single-layer MXene two-dimensional nanosheet + chitosan + phase change microcapsule); the single-layer MXene two-dimensional nanosheet and chitosan can fix the phase change microcapsule in the framework structure, and have good stability. Figure 2 It can be seen that with the addition of chitosan, the interlayer spacing is significantly reduced and the interlayer bonding force is significantly increased. And the SEM image shows that the phase change microcapsules are located in the middle layer between the single-layer MXene two-dimensional nanosheet and chitosan, and the greater the content of the phase change microcapsules, the greater the interlayer spacing between the single-layer MXene two-dimensional nanosheet and chitosan.
[0038] Figure 3 The DSC curves of eicosane, phase change microcapsules and composite films of the present invention are shown. The phase change behavior and thermal storage performance of the composite film in the range of 20-60°C are studied through the DSC curves. It can be seen from the figure that the composite film produces a melting peak and two crystallization peaks during the melting and crystallization processes, respectively, and the preparation process of the composite film has no effect on the phase change behavior of the phase change microcapsules. Its good thermal performance provides a strong guarantee for the application of composite films in thermal management.
[0039] Figure 4 The thermogravimetric curve of the composite membrane of the present invention is shown in FIG. 1 . TG analysis shows that the composite membrane has almost no mass loss in the range of 30-100° C., which proves that the composite membrane has good thermal stability at the working temperature.
[0040] Figure 5The simulated thermal management curve of the composite film of the present invention is shown in Figure 2. Two identical fabrics are placed in a constant low temperature environment, and the composite film is attached to the center of the surface of one of the fabrics. The fabrics are irradiated with simulated sunlight, and it is found that the surface temperature of the fabric with the composite film attached is about 18°C higher than that of the fabric without the composite film. After removing the solar radiation cooling, the latent heat released by the phase change material in the composite film can delay the temperature drop to achieve the thermal management effect. It can be seen that the composite film has good thermal management performance.
[0041] In summary, the multifunctional phase-change composite film with thermal management performance prepared by the present invention can be applied to thermal insulation materials and human photothermal therapy, and has a suitable phase change temperature, excellent phase change enthalpy and good thermal stability. In addition, the reaction process is simple and easy to control, the production cycle is short, and the production cost is low.
[0042] Embodiment 2:
[0043] The present invention provides a method for preparing a multifunctional phase-change composite film with thermal management performance, comprising the following steps:
[0044] S1. Preparation of phase change microcapsules
[0045] 5g of phase change material, 0.8g of hexadecyltrimethylammonium bromide as a cationic surfactant and 60mL of formamide as a dispersion medium were mixed in a three-necked flask at 60°C and heated in a water bath with stirring for 4 hours. Then, 5g of tetraethoxysilane was added to the mixture as a silicon source, and then stirred continuously for 5h. Subsequently, 60mL of aqueous hydrochloric acid solution was dripped into the flask, stirred vigorously for 4 hours, and then aged at 50°C for 24 hours. The synthesized product was filtered, washed with deionized water and alcohol, and then dried at 35°C for 24 hours to obtain the phase change microcapsule product SiO2-MEPCM;
[0046] S2. Preparation of Monolayer MXene
[0047] Ti3C2T was prepared by mixed acid etching x , pour the etchant and deionized water into the polytetrafluoroethylene liner and heat and stir in a water bath for 30 minutes, then add 1g Ti3AlC2 in small amounts several times, stir for 24 hours, collect the solution and centrifuge until the pH of the solution is neutral, then add 2g LiCl to the above solution and stir for 24 hours in a water bath heated at 50°C. Collect the solution and centrifuge it several times to obtain a single-layer MXene two-dimensional nanosheet.
[0048] S3. Preparation of composite membrane
[0049] 25.7 ml of 0.7 mg / mL monolayer MXene two-dimensional nanosheet solution was mixed with 1.8 g of chitosan solution and stirred for 1 h, and then the phase change microcapsule product was added and ultrasonicated to obtain a uniform mixture. Finally, the composite membrane was obtained by vacuum filtration.
[0050] In step S1, the phase change material is any one of hexadecane, octadecane, and eicosane, the ratio of the phase change material to tetraethoxysilane is 1:1, and the concentration of the added hydrochloric acid aqueous solution is 0.8M.
[0051] In step S2, the etchant is a mixed solution of fluoride and hydrochloric acid, wherein the fluoride is any one of sodium fluoride and lithium fluoride, the mass ratio of fluoride to MAX phase material is 1:1, and the concentration of hydrochloric acid is 12 mol / L.
[0052] Comparative Example 1:
[0053] Comparative Example 1 adopts “A multifunctional flexible composite phase-change film with excellent solar driven thermal management, Renewable Energy” proposed by Kuan Zhao, Jifen Wang, Huaqing Xie et al. in “Renewable Energy”.
[0054] Comparative Example 2:
[0055] Comparative Example 2 adopts “A dual cooling composite film by subtly combining phase change materials and thermally conductive fillers for efficient thermal management” proposed by Ni Shi Hao, Hu Yu Fan, Huang Yu Chuan, Wang Shuai Peng, Zhou Yun Hong et al. in Journal of Materials Science.
[0056] Comparative Example 3:
[0057] Comparative Example 3 adopts "Synthesis and properties of multifunctional microencapsulated phase change material for intelligent textiles" proposed by Li Jun, Zhu Xiaoyun, Wang Huichang, Lin Pengcheng, Jia Lisi, Li Longjian, Chen Ying et al. in "Journal of Materials Science".
[0058] Comparative Example 4:
[0059] Comparative Example 4 adopts “Preparation of phase change microcapsules-aerogels composites and the enhanced thermal properties” proposed by Jing Li, Yiting Zhang, Zhongbi Zhang, Hongli Liu, Jianming Rui, Yajing Li, Zhong Chen et al. in Materials Letters.
[0060] Comparative Example 5:
[0061] Comparative Example 5 adopts "Preparation of n-Tetradecane Phase Change Microencapsulated Polyurethane Coating and Experiment on Anti-Icing Performance for Wind Turbine Blades" proposed by Yiting Wang; He Shen; Zheng Sun; Yan Li; Fang Feng. et al. in "Coatings".
[0062] The phase change enthalpy of the composite material prepared in Example 1 of the present invention is compared with that of Comparative Examples 1 to 5. The results are shown in Table 1. The results show that the MXene / CS / PCC composite material disclosed in the present invention has excellent heat storage capacity, can effectively store heat energy during the phase change process, and adjust the temperature to achieve a thermal management effect. The specific content of Table 1 is as follows:
[0063] Table 1 Comparison of phase change enthalpy of different composite materials
[0064]
[0065]
[0066] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a multifunctional phase-change energy storage composite film with thermal management performance, characterized in that: The following steps are involved: S1. Preparation of phase change microcapsules Phase change material, hexadecyltrimethylammonium bromide and formamide are mixed in a three-necked flask and heated in a water bath with stirring. Then, tetraethoxysilane is added to the mixture and continued to heat and stir. Subsequently, aqueous hydrochloric acid solution is dripped into the flask, stirred vigorously and aged. Finally, the synthesized product is filtered, washed and dried to obtain a phase change microcapsule product SiO2-MEPCM with excellent thermal storage performance. S2. Preparation of Monolayer MXene Ti3C2T was prepared by mixed acid etching x , pour the etchant and deionized water into a polytetrafluoroethylene liner for heating and stirring in a water bath, then add Ti3AlC2 in small amounts and multiple times, collect the solution and centrifuge until the pH of the solution is neutral, then add LiCl to the above solution and stir, collect the solution and centrifuge it several times, and the result is a single-layer MXene two-dimensional nanosheet; S3. Preparation of composite membrane The single-layer MXene two-dimensional nanosheet solution and the chitosan solution were mixed and stirred, and then the phase change microcapsule product was added and ultrasonicated to obtain a uniform mixture. Finally, vacuum filtration was performed to obtain a phase change energy storage composite film that can be used in thermal insulation materials and human photothermal therapy and has a suitable phase change temperature, excellent heat storage capacity and good thermal stability.
2. The method for preparing a multifunctional energy storage phase change composite film with thermal management performance according to claim 1, characterized in that: In the step S1, the phase change material is any one of hexadecane, octadecane and eicosane, the ratio of the phase change material to tetraethoxysilane is 1:1, the concentration of the added hydrochloric acid aqueous solution is 0.8M, and the water bath temperature is 50-60°C.
3. The method for preparing a multifunctional energy storage phase change composite film with thermal management performance according to claim 1, characterized in that: In the step S2, the etchant used is a mixed solution of fluoride and hydrochloric acid, wherein the fluoride is any one of sodium fluoride and lithium fluoride, the concentration of the hydrochloric acid is 9 mol / L to 12 mol / L, and the water bath heating temperature is 40 to 50°C.
4. The method for preparing a multifunctional phase change composite film with thermal management performance according to claim 1, characterized in that: The single-layer MXene two-dimensional nanosheet is a two-dimensional regular sheet structure, and the thickness of the single-layer MXene two-dimensional nanosheet is 1.5 to 30 nm and the diameter is 2 to 10 μm; the surface of the phase change microcapsule product is smooth and the diameter is 2.5 to 3.5 μm.